Effect of postpartum propylene glycol allocation to over-conditioned Holstein cows on concentrations of milk metabolites. Issue 2 (1st April 2016) - Bjerre-Harpøth, Vibeke; Storm, Adam C.; Vestergaard, Mogens; Larsen, Mogens; Larsen, Torben
Abstract : The objective of the study was to investigate the effect of propylene glycol (PG) allocation on concentrations of milk metabolites with potential use as indicators of glucogenic status in high yielding postpartum dairy cows. At time of calving, nine ruminally cannulated Holstein cows were randomly assigned to ruminal dosing of 500 g/d tap water (CON, n = 4) or 500 g/d PG (PPG, n = 5). The PG was given with the morning feeding week 1–4 postpartum (treatment period) and cows were further followed during week 5–8 postpartum (follow-up period). All cows were fed the same postpartum diet. Milk samples were obtained at each milking (3 times/d) in the treatment period, and at morning milking during the follow-up period. Weekly blood samples were obtained from –4 to +8 weeks relative to calving and daily blood samples from –7 until +7 d relative to calving. The main effect of PG allocation was an increased glucogenic status, e.g. visualised by a prompt marked increase in blood fructosamine. During the treatment period, milk concentration of free glucose tended to be greater, whereas milk concentrations of isocitrate and BHBA were lower for PPG compared with CON. It is proposed that the ratio between free glucose and isocitrate in milk may be a potential biomarker for glucogenic status in the vulnerable early postpartum period. We will pursue this issue in the future.